2009
DOI: 10.1186/1471-2407-9-12
|View full text |Cite
|
Sign up to set email alerts
|

Paxillin-Y118 phosphorylation contributes to the control of Src-induced anchorage-independent growth by FAK and adhesion

Abstract: BackgroundFocal adhesion kinase (FAK) and Src are protein tyrosine kinases that physically and functionally interact to facilitate cancer progression by regulating oncogenic processes such as cell motility, survival, proliferation, invasiveness, and angiogenesis.MethodTo understand how FAK affects oncogenesis through the phosphorylation of cellular substrates of Src, we analyzed the phosphorylation profile of a panel of Src substrates in parental and v-Src-expressing FAK+/+ and FAK-/- mouse embryo fibroblasts,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
39
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 63 publications
7
39
0
Order By: Relevance
“…FAK, and the related protein, CAKβ/Pyk2/CadTK/RAFTK, have not only been shown to physically interact and co-localize with paxillin in vivo, but the activation and/or overexpression of these tyrosine kinases has been implicated in an increased proportion of tyrosine phosphorylated paxillin [86,111,112]. Specifically, studies have shown that the relative levels of paxillin Y31 and Y118 phosphorylation are reduced in FAK -/-MEFs in comparison to wildtype FAK +/+, with additional studies demonstrating complete inhibition of paxillin tyrosine phosphorylation via overexpression of dominant negative FAK; inflated levels of paxillin tyrosine phosphorylation in the FAK -/-is believed to be the result of the compensatory expression of CAKβ in these cells [83,86,109].…”
Section: Paxillin Tyrosine Phosphorylationmentioning
confidence: 99%
See 1 more Smart Citation
“…FAK, and the related protein, CAKβ/Pyk2/CadTK/RAFTK, have not only been shown to physically interact and co-localize with paxillin in vivo, but the activation and/or overexpression of these tyrosine kinases has been implicated in an increased proportion of tyrosine phosphorylated paxillin [86,111,112]. Specifically, studies have shown that the relative levels of paxillin Y31 and Y118 phosphorylation are reduced in FAK -/-MEFs in comparison to wildtype FAK +/+, with additional studies demonstrating complete inhibition of paxillin tyrosine phosphorylation via overexpression of dominant negative FAK; inflated levels of paxillin tyrosine phosphorylation in the FAK -/-is believed to be the result of the compensatory expression of CAKβ in these cells [83,86,109].…”
Section: Paxillin Tyrosine Phosphorylationmentioning
confidence: 99%
“…Differential paxillin phosphorylation within the focal adhesion has been shown to mediate focal adhesion assembly and disassembly [139,140]. Specifically, serine phosphorylation of the LIM domain of paxillin has been found to temporally target and/or regulate the integration of paxillin into focal adhesions while tyrosine phosphorylated paxillin has been shown to recruit the focal adhesion proteins FAK and Src into the adhesion complex [99,110,111]. Actively disassembling adhesions, such as early adhesions and the distal part of late adhesions, are preferential zones of microtubule targeting and catastrophe that have been shown to be enriched in phosphorylated paxillin [22,30,110,140].…”
Section: Autorad Chaptermentioning
confidence: 99%
“…Paxillin dynamics are regulated by several proteins including FAK [22][23][24]. We previously showed that both paxillin and FAK were rapidly phosphorylated following leukocyte adhesion under flow conditions [19] and we and others have also shown that FAK redistributes during neutrophil transmigration [18] (Supporting Information Fig.…”
Section: Disrupting Fak and Fak Signaling Blocks Neutrophil Transmigrmentioning
confidence: 99%
“…To test adhesion of ECs to ECM after in vivo Cdc42 depletion, we assessed the focal adhesion marker phosphorylated Paxillin ( pPax, Y118; pPxn -Mouse Genome Informatics) (Sachdev et al, 2009). Cdc42…”
Section: Cdc42 Regulates Ec Adhesionmentioning
confidence: 99%